Humoral and cellular immunity to RSV in infants, children and adults. Issue 41 (1st October 2018) - Green, C.A.; Sande, C.J.; de Lara, C.; Thompson, A.J.; Silva-Reyes, L.; Napolitano, F.; Pierantoni, A.; Capone, S.; Vitelli, A.; Klenerman, P.; Pollard, A.J.
Abstract: Background: Respiratory syncytial virus (RSV) causes respiratory disease throughout life. Here we report differences in naturally acquired immunity with age and presumed exposure. Methods: A longitudinal, non-interventional, observational study was performed in healthy adults (20 paediatric healthcare workers and 10 non-healthcare workers), children (10 aged 3–6 years) and infants (5 aged 2–4 months and 20 aged 6–12 months). Blood samples were analysed for RSV-neutralising antibody titre, F/Ga/Gb-specific antibody titres, F-specific IgG/IgA memory B-cell frequencies and T-cell production of IFNγ, IL-4, IL-13 and IL-17. Results: Serum G-specific antibody titres were significantly lower in infants and children than adults. However, serum titres of F-specific and RSV-neutralising antibody and IFNγ-producing T-cell frequencies were low or absent in the infants, but comparable between children and adults. Interestingly, F-specific memory IgA B-cells could not be detected in paediatric samples and in samples from non-healthcare workers, but recordable IgA memory B-cells were found in 9/18 paediatric healthcare workers and 2/8 non-healthcare workers at the end of the RSV season. These responses waned 4–6 months later. By contrast, F-specific IgG memory B-cells were detectable in samples from all adults without significant variation across time points. T-cells producing IL-4, IL-13 and IL-17 responses were not detectable in peripheral blood from a subset of volunteers. Conclusions: Repeated RSV exposure in early life generates immune responses that are inversely related to frequency of severe disease. Induction of F-specific antibody and cellular immune responses through infant vaccination might help to accelerate the development of protective immune responses at an early age. Clinicaltrials.gov referenceNCT01563692 andNCT01640652 .